INTERIOR TEXTILES WITH SHIELDING PROPERTIES AGAINST ELECTROMAGNETIC RADIATION - Арабулі, С. І.; Кизимчук, О. П.; Арабулі, А. Т.; Власенко, В. І.; Байзік, В.; Очеретна, Л. В.; Тунак, М. (Art and Design, 2020)
The purpose. An investigation of the shielding effectiveness against electromagnetic radiation (EMR) by woven fabrics that are presented on the Ukrainian interior textile market. Methodology. Theoretical and experimental research is based on the general principles of textile materials science. The shielding effectiveness to EMR of textile fabrics was tested and measured using EM-2107A (Electro Metrics) in accordance with ASTM 4935-10 in the frequency range 30 MHz – 1.5 GHz. Results. Flexible screens based on textile materials are widely used for EMR shielding. The shielding effectiveness against EMR by textile materials can be improved with fabric modifying by metal fibers/threads, metal particles or conductive polymers at various stages of textile production. It possible to substantiate the expediency of using metal-containing textile materials as interior textiles on the result of carried out analysis of the modern assortment of interior textiles and the experimental studies. Studies results have shown that the proposed fabrics have a high shielding ability by the classification "professional use" according to FTTS-FA-003 Specified Requirements of Electromagnetic Shielding Textiles, the shielding efficiency of which is within 30 ÷ 60 dB. Scientific novelty. The expediency of using modern metal-containing textile materials as interior textiles for windows decoration has been substantiated. The studied textile materials make it possible to clarify a new promising segment of the interior textile market - windows decoration. The main goal of such textile - the decoration of the residential and administrative buildings is expanded and supplemented by the function of electromagnetic radiation shielding. Practical significance. The complex of scientific research on the shielding effectiveness against EMR allowed offering a new range of interior textile materials for window decoration.